Systems and Software Interface Survey. Issue 2 (6th August 2021) - Muscarella, Sally; Osaisai, Macaulay; Sheard, Sarah
ABSTRACT: INCOSE formed the Systems and Software Interface Working Group (SaSIWG) in 2017, responding to the Corporate Advisory Board interest in software and problems identified in the systems and software interface (physical, logical, data, and human). This third SaSIWG paper presents a systems engineers, software engineers, and project managers survey discussing best practices and the priority challenges related to the interface between systems and software. We group and summarize the best practices mentioned by the 31 interviewees then address priority challenges and problems. Systems engineering done well includes an ever‐increasing amount of Model‐Based Systems Engineering. It also includes developing and holding to a vision, managing data, ensuring inter‐disciplinary work, planning systematic verification, and ensuring modularity. Systems engineering must evolve to meet new challenges and, most importantly, systems engineer expertise must include software engineering.